Survey of graduates' criteria for success in life - Hofer, Raffaella (Animo Repository, 1967)
This study analyzes the value choices of some graduates of the College of the Holy Spirit and relates these choices to the objectives and purposes of the school. Eighty seven out of 196 of the school's 1966-67 graduates were the subjects of this study. The study made use of an unstructured stimulus situation as a means to elicit responses from the subjects of the study. The six main categories of success criteria developed empirically from the responses gathered were supernatural, moral, socio-cultural, personal, professional, and economic. Based on the findings of the study, it was concluded that the objectives and ideals of the College of the Holy Spirit were evident in the value choices of the graduates. It was found that in the context of the school's objectives the value of moral worth was selected most frequently. Social-cultural values, which were not particularly stressed by the school, were highly prized by the subjects. Also, a thorough re-evaluation and re-formulation of the objectives and ideals of the College of the Holy Spirit seemed advisable.